Survival and harvest‐related mortality of white‐tailed deer in massachusetts - John E. Mcdonald Jr.; Stephen Destefano; Christopher Gaughan; Michael Mayer; William A. Woytek; Sonja Christensen; Todd K. Fuller (Wildlife Society Bulletin, 2011)
Abstract We monitored 142 radiocollared adult (≥1.0 yr old) white‐tailed deer (Odocoileus virginianus) in 3 study areas of Massachusetts, USA, to estimate annual survival and mortality due to legal hunting. We then applied these rates to deer harvest information to estimate deer population trends over time, and compared these to trends derived solely from harvest data estimates. Estimated adult female survival rates were similar (0.82–0.86), and uniformly high, across 3 management zones in Massachusetts that differed in landscape composition, human density, and harvest regulations. Legal hunting accounted for 16–29% of all adult female mortality. Estimated adult male survival rates varied from 0.55 to 0.79, and legal hunting accounted for 40–75% of all mortality. Use of composite hunting mortality rates produced realistic estimates for adult deer populations in 2 zones, but not for the third, where estimation was hindered by regulatory restrictions on antlerless deer harvest. In addition, the population estimates we calculated were generally higher than those derived from population reconstruction, likely due to relatively low harvest pressure. Legal harvest may not be the dominant form of deer mortality in developed landscapes; thus, estimates of populations or trends that rely solely on harvest data will likely be underestimates. © 2011 The Wildlife Society.